2008
DOI: 10.1007/s11524-008-9312-9
|View full text |Cite
|
Sign up to set email alerts
|

The North American Opiate Medication Initiative (NAOMI): Profile of Participants in North America’s First Trial of Heroin-Assisted Treatment

Abstract: Standardized assessment instruments such as the European Addiction Severity Index and the Maudsley Addiction Profile were employed. A total of 251 individuals were randomized from Vancouver, BC (192, 76.5%), and Montreal, Quebec (59, 23.5%); 38.5% were female, the mean age was 39.7 years (SD:8.6), and participants had injected drugs for 16.5 years (SD:9.9), on average. In the prior month, heroin was used a mean of 26.5 days (SD:7.4) and cocaine 16 days (SD;12.6). Vancouver had significantly more patients resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 64 publications
1
36
0
Order By: Relevance
“…Detailed inclusion and exclusion criteria and baseline characteristics of the study participants have been published previously. 23,28 In brief, at baseline, the study participants were 25 years or older, with regular opioid injection, a minimum five-year history of opioid use, and at least two previous attempts at substitution treatment for opioid dependence. The average age of the participants was 39.7 years, and 61.4% were men.…”
Section: Model Designmentioning
confidence: 99%
“…Detailed inclusion and exclusion criteria and baseline characteristics of the study participants have been published previously. 23,28 In brief, at baseline, the study participants were 25 years or older, with regular opioid injection, a minimum five-year history of opioid use, and at least two previous attempts at substitution treatment for opioid dependence. The average age of the participants was 39.7 years, and 61.4% were men.…”
Section: Model Designmentioning
confidence: 99%
“…Compared to participants in other trials [13,14,[16][17][18][19]22], our participants showed the same level of criminal involvement in the past but were less involved in illegal activities at baseline (Table 3). The main crimes committed by our population were acquisitive crime.…”
Section: Discussionmentioning
confidence: 56%
“…The German trial had an entry criterion of 'poor physical and/or mental health with at least 13 symptoms on the Opiate Treatment Index OTI' [9], and the Dutch trials had an entry criterion of 'poor physical or mental health', including those not stabilized on psychiatric medication [10], while in RIOTT any 'active significant medical or psychiatric condition' was excluded [11]. Participants were recruited from methadone programmes [1,10], but also from the street being out of treatment [9,12,13]. The following instruments for initial assessments were used: DSM-IV [10], Symptom Checklist Index-90 (SCL-90) [10], SCL-90-R [9], Opiate Treatment Index (OTI) [9,12], Short Form (SF)-12 [12], Addiction Severity Index (ASI) [12], Europ-ASI [13] and the SF Health Survey [14], plus diverse laboratory data.…”
Section: About Comparing Outcomes Across Trialsmentioning
confidence: 99%
“…Participants were recruited from methadone programmes [1,10], but also from the street being out of treatment [9,12,13]. The following instruments for initial assessments were used: DSM-IV [10], Symptom Checklist Index-90 (SCL-90) [10], SCL-90-R [9], Opiate Treatment Index (OTI) [9,12], Short Form (SF)-12 [12], Addiction Severity Index (ASI) [12], Europ-ASI [13] and the SF Health Survey [14], plus diverse laboratory data. Outcome measurements and responder definition varied across trials ( [15], p. 38), and differences in treatment regimens were substantial with regard to dosages ([15], p. 39).…”
Section: About Comparing Outcomes Across Trialsmentioning
confidence: 99%